Global gene expression response of a population exposed to benzene: A pilot study exploring the use of RNA‐sequencing technology. (1st August 2013) - Thomas, Reuben; McHale, Cliona M.; Lan, Qing; Hubbard, Alan E.; Zhang, Luoping; Vermeulen, Roel; Li, Guilan; Rappaport, Stephen M.; Yin, Songnian; Rothman, Nathaniel; Smith, Martyn T.
<x xml:space="preserve">Abstract</x> The mechanism of toxicity of the leukemogen benzene is not entirely known. This pilot study used RNA‐sequencing (RNA‐seq) technology to examine the effect of benzene exposure on gene expression in peripheral blood mononuclear cells obtained from 10 workers occupationally exposed to high levels of benzene (≥5 ppm) in air and 10 matched unexposed control workers, from a large study (n = 125) in which gene expression was previously measured by microarray. RNA‐seq is more sensitive and has a wider dynamic range for the quantification of gene expression. Further, it has the ability to detect novel transcripts and alternative splice variants. The main conclusions from our analysis of the 20 workers by RNA‐seq are as follows: The Pearson correlation between the two technical replicates for the RNA‐seq experiments was 0.98 and the correlation between RNA‐seq and microarray signals for the 20 subjects was around 0.6. 60% of the transcripts with detected reads from the RNA‐seq experiments did not have corresponding probes on the microarrays. Fifty‐three percent of the transcripts detected by RNA‐seq and 99% of those with probes on the microarray were protein‐coding. There was a significant overlap (P < 0.05) in transcripts declared differentially expressed due to benzene exposure using the two technologies. About 20% of the transcripts declared differentially expressed using the RNA‐seq data were non‐coding transcripts. Six transcripts were determined (false‐discovery rate < 0.05) to be alternatively spliced as a result of benzene exposure. Overall, this pilot study shows that RNA‐seq can complement the information obtained by microarray in the analysis of changes in transcript expression from chemical exposures. Environ. Mol. Mutagen. 54:566‐573, 2013. © 2013 Wiley Periodicals, Inc.